(untitled) (Bangladesh Journal of Medical Biochemistry, 2014)
Risk of coronary heart disease and other forms of atherosclerotic vascular diseases, rises with plasma cholesterol concentration and in particular with the rise of ratio of total cholesterol to high density lipoprotein (HDL-C) cholesterol. A much weaker correlation also exists with plasma triglyceride concentration. Extensive large-scale randomized trials have shown that lowering total cholesterol and LDL-C concentrations reduces the risk of cardiovascular events including death, myocardial infarction and stroke and reduces the need for revascularisation.This cross-sectional analytical study was designed to observe association between lipid profile level with chronic ischaemic heart disease and the study was conducted in the Department of Biochemistry, Dhaka Medical College, Dhaka from July 2010 to June 2011. A total of 50 cases were selected purposively according to the selection criteria from the patients admitted in the Department of Cardiology, Dhaka Medical College Hospital with chronic ischaemic heart disease (IHD). Diagnosed IHD patients were taken as cases and 50 age- & sex- matched healthy subjects were taken as controls. Serum TC, TG, LDL-C & HDL-C were measured in all study subjects.The mean±SD of serum TC, TG, HDL-C and LDL-C concentration in cases were 314.54±73.72 mg/dl, 288.04±60.45 mg/dl, 36.02±4.12 mg/dl, and 178.62±22.7 mg/dl respectively and in controls were 174.64±18.97 mg/dl, 119.42±12.47 mg/dl, 43.04±2.58 mg/dl & 126.28±11.45 mg/dl respectively. Serum Total Cholesterol, TG & LDL-C were found to be significantly higher in cases than that of controls. Serum HDL-C was found to be significantly lower in cases than that of controls. The present study reveals that the patients with chronic ischemic heart disease is accociated with significantly higher levels of serum TC, TG and LDL-C whereas HDL-C was found to be lower in IHD patients. DOI: http://dx.doi.org/10.3329/bjmb.v7i1.18574 Bangladesh J Med Biochem 2014; 7(1): 14-16